Bahan Organik Tanah pada Sawah dengan Pola Tanam Padi - Padi dan Padi - Palawija di Kecamatan Pagar Alam Selatan Kota Pagar Alam - Bakri, Bakri; Prayitno, Muh Bambang; Narendra Dirgantara, Altalaric (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2022)
Bakri B, Prayitno MH, Dirgantara AN. 2022. Soil Organic matter distribution in rice fields with rice - rice and rice - palawija crop rotation at subdistrict Pagar Alam Selatan, Pagar Alam City. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 143-152. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The aimed of the study was to compare the levels of soil organic matter in cultivated paddy fields with rice-paddy and rice-palawija cropping patterns in Pagar Alam Selatan District, Pagar Alam City. This research was conducted in Pagar Alam Selatan District, Pagar Alam City and soil analysis was carried out at the Laboratory of Chemistry, Biology and Soil Fertility, Faculty of Agriculture, Sriwijaya University. Sampling was carried out using a grid survey method with a detailed survey level to compare between treatments using the T test. The parameter measured was C-organic analyzed by the Walkey and Black method. The results showed that the levels of organic matter in the two paddy fields in Pagar Alam Selatan District, Pagar Alam City were very high with the average soil organic matter content in paddy fields with a rice-paddy cropping pattern of 11.96% and an average organic matter content of 11.96%. soil in paddy fields with rice-crop crops pattern is 9.96%. The organic matter content of paddy fields with rice-paddy cropping patterns was significantly different from that of paddy-palawija cropping patterns.